DEFINITION sn3_appl_lref()
TYPE =
       c:C
         .i:nat
           .nf2 c (TLRef i)
             v:T.(sn3 c v)(sn3 c (THead (Flat Appl) v (TLRef i)))
BODY =
        assume cC
        assume inat
        suppose Hnf2 c (TLRef i)
        assume vT
        suppose H0sn3 c v
          we proceed by induction on H0 to prove sn3 c (THead (Flat Appl) v (TLRef i))
             case sn3_sing : t1:T :t2:T.((eq T t1 t2)P:Prop.P)(pr3 c t1 t2)(sn3 c t2) 
                the thesis becomes sn3 c (THead (Flat Appl) t1 (TLRef i))
                (H2) by induction hypothesis we know 
                   t2:T
                     .(eq T t1 t2)P:Prop.P
                       (pr3 c t1 t2)(sn3 c (THead (Flat Appl) t2 (TLRef i)))
                    assume t2T
                    suppose H3(eq T (THead (Flat Appl) t1 (TLRef i)) t2)P:Prop.P
                    suppose H4pr2 c (THead (Flat Appl) t1 (TLRef i)) t2
                      (H5
                         by (pr2_gen_appl . . . . H4)

                            or3
                              ex3_2 T T λu2:T.λt2:T.eq T t2 (THead (Flat Appl) u2 t2) λu2:T.λ:T.pr2 c t1 u2 λ:T.λt2:T.pr2 c (TLRef i) t2
                              ex4_4
                                T
                                T
                                T
                                T
                                λy1:T.λz1:T.λ:T.λ:T.eq T (TLRef i) (THead (Bind Abst) y1 z1)
                                λ:T.λ:T.λu2:T.λt2:T.eq T t2 (THead (Bind Abbr) u2 t2)
                                λ:T.λ:T.λu2:T.λ:T.pr2 c t1 u2
                                λ:T.λz1:T.λ:T.λt2:T.b:B.u:T.(pr2 (CHead c (Bind b) u) z1 t2)
                              ex6_6
                                B
                                T
                                T
                                T
                                T
                                T
                                λb:B.λ:T.λ:T.λ:T.λ:T.λ:T.not (eq B b Abst)
                                λb:B.λy1:T.λz1:T.λ:T.λ:T.λ:T.eq T (TLRef i) (THead (Bind b) y1 z1)
                                λb:B
                                  .λ:T
                                    .λ:T
                                      .λz2:T
                                        .λu2:T
                                          .λy2:T.eq T t2 (THead (Bind b) y2 (THead (Flat Appl) (lift (S OO u2) z2))
                                λ:B.λ:T.λ:T.λ:T.λu2:T.λ:T.pr2 c t1 u2
                                λ:B.λy1:T.λ:T.λ:T.λ:T.λy2:T.pr2 c y1 y2
                                λb:B.λ:T.λz1:T.λz2:T.λ:T.λy2:T.pr2 (CHead c (Bind b) y2) z1 z2
                      end of H5
                      we proceed by induction on H5 to prove sn3 c t2
                         case or3_intro0 : H6:ex3_2 T T λu2:T.λt3:T.eq T t2 (THead (Flat Appl) u2 t3) λu2:T.λ:T.pr2 c t1 u2 λ:T.λt3:T.pr2 c (TLRef i) t3 
                            the thesis becomes sn3 c t2
                               we proceed by induction on H6 to prove sn3 c t2
                                  case ex3_2_intro : x0:T x1:T H7:eq T t2 (THead (Flat Appl) x0 x1) H8:pr2 c t1 x0 H9:pr2 c (TLRef i) x1 
                                     the thesis becomes sn3 c t2
                                        (H10
                                           we proceed by induction on H7 to prove 
                                              eq T (THead (Flat Appl) t1 (TLRef i)) (THead (Flat Appl) x0 x1)
                                                P:Prop.P
                                              case refl_equal : 
                                                 the thesis becomes the hypothesis H3

                                              eq T (THead (Flat Appl) t1 (TLRef i)) (THead (Flat Appl) x0 x1)
                                                P:Prop.P
                                        end of H10
                                        (H11
                                           by (H . H9)
                                           we proved eq T (TLRef i) x1
                                           by (eq_ind_r . . . H10 . previous)

                                              (eq
                                                  T
                                                  THead (Flat Appl) t1 (TLRef i)
                                                  THead (Flat Appl) x0 (TLRef i))
                                                P:Prop.P
                                        end of H11
                                        by (H . H9)
                                        we proved eq T (TLRef i) x1
                                        we proceed by induction on the previous result to prove sn3 c (THead (Flat Appl) x0 x1)
                                           case refl_equal : 
                                              the thesis becomes sn3 c (THead (Flat Appl) x0 (TLRef i))
                                                 (H_x
                                                    by (term_dec . .)
or (eq T t1 x0) (eq T t1 x0)P:Prop.P
                                                 end of H_x
                                                 (H13consider H_x
                                                 we proceed by induction on H13 to prove sn3 c (THead (Flat Appl) x0 (TLRef i))
                                                    case or_introl : H14:eq T t1 x0 
                                                       the thesis becomes sn3 c (THead (Flat Appl) x0 (TLRef i))
                                                          (H15
                                                             by (eq_ind_r . . . H11 . H14)

                                                                (eq
                                                                    T
                                                                    THead (Flat Appl) t1 (TLRef i)
                                                                    THead (Flat Appl) t1 (TLRef i))
                                                                  P:Prop.P
                                                          end of H15
                                                          we proceed by induction on H14 to prove sn3 c (THead (Flat Appl) x0 (TLRef i))
                                                             case refl_equal : 
                                                                the thesis becomes sn3 c (THead (Flat Appl) t1 (TLRef i))
                                                                   by (refl_equal . .)
                                                                   we proved 
                                                                      eq
                                                                        T
                                                                        THead (Flat Appl) t1 (TLRef i)
                                                                        THead (Flat Appl) t1 (TLRef i)
                                                                   by (H15 previous .)
sn3 c (THead (Flat Appl) t1 (TLRef i))
sn3 c (THead (Flat Appl) x0 (TLRef i))
                                                    case or_intror : H14:(eq T t1 x0)P:Prop.P 
                                                       the thesis becomes sn3 c (THead (Flat Appl) x0 (TLRef i))
                                                          by (pr3_pr2 . . . H8)
                                                          we proved pr3 c t1 x0
                                                          by (H2 . H14 previous)
sn3 c (THead (Flat Appl) x0 (TLRef i))
sn3 c (THead (Flat Appl) x0 (TLRef i))
                                        we proved sn3 c (THead (Flat Appl) x0 x1)
                                        by (eq_ind_r . . . previous . H7)
sn3 c t2
sn3 c t2
                         case or3_intro1 : H6:ex4_4 T T T T λy1:T.λz1:T.λ:T.λ:T.eq T (TLRef i) (THead (Bind Abst) y1 z1) λ:T.λ:T.λu2:T.λt3:T.eq T t2 (THead (Bind Abbr) u2 t3) λ:T.λ:T.λu2:T.λ:T.pr2 c t1 u2 λ:T.λz1:T.λ:T.λt3:T.b:B.u:T.(pr2 (CHead c (Bind b) u) z1 t3) 
                            the thesis becomes sn3 c t2
                               we proceed by induction on H6 to prove sn3 c t2
                                  case ex4_4_intro : x0:T x1:T x2:T x3:T H7:eq T (TLRef i) (THead (Bind Abst) x0 x1) H8:eq T t2 (THead (Bind Abbr) x2 x3) :pr2 c t1 x2 :b:B.u:T.(pr2 (CHead c (Bind b) u) x1 x3) 
                                     the thesis becomes sn3 c t2
                                        (H12
                                           we proceed by induction on H7 to prove 
                                              <λ:T.Prop>
                                                CASE THead (Bind Abst) x0 x1 OF
                                                  TSort False
                                                | TLRef True
                                                | THead   False
                                              case refl_equal : 
                                                 the thesis becomes 
                                                 <λ:T.Prop>
                                                   CASE TLRef i OF
                                                     TSort False
                                                   | TLRef True
                                                   | THead   False
                                                    consider I
                                                    we proved True

                                                       <λ:T.Prop>
                                                         CASE TLRef i OF
                                                           TSort False
                                                         | TLRef True
                                                         | THead   False

                                              <λ:T.Prop>
                                                CASE THead (Bind Abst) x0 x1 OF
                                                  TSort False
                                                | TLRef True
                                                | THead   False
                                        end of H12
                                        consider H12
                                        we proved 
                                           <λ:T.Prop>
                                             CASE THead (Bind Abst) x0 x1 OF
                                               TSort False
                                             | TLRef True
                                             | THead   False
                                        that is equivalent to False
                                        we proceed by induction on the previous result to prove sn3 c (THead (Bind Abbr) x2 x3)
                                        we proved sn3 c (THead (Bind Abbr) x2 x3)
                                        by (eq_ind_r . . . previous . H8)
sn3 c t2
sn3 c t2
                         case or3_intro2 : H6:ex6_6 B T T T T T λb:B.λ:T.λ:T.λ:T.λ:T.λ:T.not (eq B b Abstλb:B.λy1:T.λz1:T.λ:T.λ:T.λ:T.eq T (TLRef i) (THead (Bind b) y1 z1) λb:B.λ:T.λ:T.λz2:T.λu2:T.λy2:T.eq T t2 (THead (Bind b) y2 (THead (Flat Appl) (lift (S OO u2) z2)) λ:B.λ:T.λ:T.λ:T.λu2:T.λ:T.pr2 c t1 u2 λ:B.λy1:T.λ:T.λ:T.λ:T.λy2:T.pr2 c y1 y2 λb:B.λ:T.λz1:T.λz2:T.λ:T.λy2:T.pr2 (CHead c (Bind b) y2) z1 z2 
                            the thesis becomes sn3 c t2
                               we proceed by induction on H6 to prove sn3 c t2
                                  case ex6_6_intro : x0:B x1:T x2:T x3:T x4:T x5:T :not (eq B x0 Abst) H8:eq T (TLRef i) (THead (Bind x0) x1 x2) H9:eq T t2 (THead (Bind x0) x5 (THead (Flat Appl) (lift (S OO x4) x3)) :pr2 c t1 x4 :pr2 c x1 x5 :pr2 (CHead c (Bind x0) x5) x2 x3 
                                     the thesis becomes sn3 c t2
                                        (H14
                                           we proceed by induction on H8 to prove 
                                              <λ:T.Prop>
                                                CASE THead (Bind x0) x1 x2 OF
                                                  TSort False
                                                | TLRef True
                                                | THead   False
                                              case refl_equal : 
                                                 the thesis becomes 
                                                 <λ:T.Prop>
                                                   CASE TLRef i OF
                                                     TSort False
                                                   | TLRef True
                                                   | THead   False
                                                    consider I
                                                    we proved True

                                                       <λ:T.Prop>
                                                         CASE TLRef i OF
                                                           TSort False
                                                         | TLRef True
                                                         | THead   False

                                              <λ:T.Prop>
                                                CASE THead (Bind x0) x1 x2 OF
                                                  TSort False
                                                | TLRef True
                                                | THead   False
                                        end of H14
                                        consider H14
                                        we proved 
                                           <λ:T.Prop>
                                             CASE THead (Bind x0) x1 x2 OF
                                               TSort False
                                             | TLRef True
                                             | THead   False
                                        that is equivalent to False
                                        we proceed by induction on the previous result to prove sn3 c (THead (Bind x0) x5 (THead (Flat Appl) (lift (S OO x4) x3))
                                        we proved sn3 c (THead (Bind x0) x5 (THead (Flat Appl) (lift (S OO x4) x3))
                                        by (eq_ind_r . . . previous . H9)
sn3 c t2
sn3 c t2
                      we proved sn3 c t2
                   we proved 
                      t2:T
                        .(eq T (THead (Flat Appl) t1 (TLRef i)) t2)P:Prop.P
                          (pr2 c (THead (Flat Appl) t1 (TLRef i)) t2)(sn3 c t2)
                   by (sn3_pr2_intro . . previous)
sn3 c (THead (Flat Appl) t1 (TLRef i))
          we proved sn3 c (THead (Flat Appl) v (TLRef i))
       we proved 
          c:C
            .i:nat
              .nf2 c (TLRef i)
                v:T.(sn3 c v)(sn3 c (THead (Flat Appl) v (TLRef i)))